Understanding durable disease resistance in rice - Lee, Seweon (Kansas State University, 2010)
Both qualitative and quantitative resistance mechanisms are important contributors to disease resistance in rice. To identify useful sources of durable resistance for Korean breeding programs, the distribution of rice blast isolates compatible to widely used resistance (R) genes was analyzed. Interactions of 3,747 Korean rice Magnaporthe oryzae isolates with eight monogenic lines, each harboring a major blast R gene, were tested. Lines with R gene Pi-9 and Pi-5 were susceptible to the fewest M. oryzae isolates, and therefore, this gene might be applied for blast resistance in breeding programs in Korea. Six major blast resistance genes were susceptible to more than 60 % of the population, suggesting limited utility of these genes in breeding programs. Quantitative trait loci (QTL)-based resistance is predicted to provide durable and broad spectrum resistance to rice diseases. A candidate gene approach was applied to a population of 164 recombinant inbred lines to identify sources of quantitative resistance. Resistance gene analogs and defense response genes were mapped on the rice chromosomes, and analyzed for their association with blast and bacterial blight resistance QTL. A total of 21 putative QTL for blast resistance were identified on chromosomes 1, 4, 5, 6, 8, 9 and 12. Four putative QTL for bacterial blight resistance were identified on chromosome 3, 5 and 10. Thirteen RGA markers were associated with 11 different QTL on chromosome 1, 5, 8, and 9. The role of one disease resistance QTL associated gene, Os02g39330, encoding a chitinase was investigated for contributing to basal defense responses. RNAi silencing was used to evaluate contributions of the gene for the resistance to Rhizoctonia solani and M. oryzae. Five transgenic lines harboring the silencing construct and which differed in the level of expression of Os02g39330 were screened for responses to R. solani and M. oryzae. The chitinase gene expression levels were inversely correlated with sheath blight disease severity, suggesting a role for this defense gene in resistance to R. solani. Rice blast disease was not affected by silencing Os02g39330. Both qualitative and QTL-based resistances provide valuable sources of disease resistance, and a combination of R gene Pi-9 and QTL harboring the Os02g39330 chitinase may help to stabilize resistance.
Keywords: durable resistance; rice; Agriculture, Plant Pathology (0480)